New regulatory challenges from cloud computing as a public utility perspective - Zsuzsanna Kosa (International Telecommunications Society (ITS), 2011)
This paper builds up a vision for regulatory framework for ICT markets from a public utility perspective. Cloud computing is considered as a tool for serving small and medium enterprises and distributed intelligent applications like intelligent transport services, health care information services or distance learning services. These applications are to be the modern service infrastructure both for business- or public-usages. Dependency of the individuals, communities and businesses is growing from the availability, affordability, safety and security of the ICT infrastructure. An innovation based, four phased business model for the infrastructure is shown. Voluntary industrial based communities may regulate themselves. Standardisation is shown as a measure for regulation to achieve a trusted agent position.
Keywords: 330; Infrastructure regulation; Cloud computing; Standardisation; Innovation